(3GdeMGSfs - (3CHj GdeMGSf eMeO Hf YHO GdhgGH Hf TYHGf Hf OGhhO GdgePGfj GdcGXej,J (B1303 (3g` s
(3ChdgG (B:s
(3CeG HYO, ajbhd GdeaJbQ Edi QMeI QHg gPG gh GdeLdO GdKGfj ef cJGH GdeMGSf, GdPj dG aj NeQ HdGZJg Zhd, hdG eGA aUGMJg BSf, hgh cJGH LeYfG ajg HYV eGdgG ef QSGFd Ldjdg s
(3BNQgG (B:s
(3BNQg eHJhQ hBNQ GdehLhO ajg(B: (3haj QeVGf bO QeGg HfGQg aChbO efg aj MTGg dXi LeQ aCeSi Yf GdChWGf hGdCgd eHYOkG bJjd dFGe GdfGS NQJ ef ZOQ s
(3HgG fXGe GdJYbjHIs
(3aj GdEfTGA hGdJQSd QJH Ydi aUhd hGHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B7 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs